Los tejedores de ensueños - Vicente Moga Romero (Mélanges de la Casa de Velázquez)
These pages seek to provide an approximation to the discourse conveyed by colonial writings in the context of the Protectorate –a look at the imagery woven by the corpus of stories of the colonisation, the rhetorical ambience in which they were set and the way the narrative line was woven by their authors. The article discusses some of the instrumental resources used to convey the distorted portrayal of the «other» in the Spanish colonial canon –the narrative keys of a discourse which was virtually seamless as regards the perceptions emanating from all social orders and classes now transformed into ideological combatants.